Dog Man the scarlet shedder - Pilkey, Dav; Falco, Phil; Geist, Ken; Newman, Jonah; Pilkey, Dav (New York Graphix, an imprint of Scholastic, 2024)
After an encounter with a skunk, Dog Man, now scarlet red after being dunked in tomato juice, is exiled but must find a way to save those who shunned him when an all-new, never-before-seen villain unleashes an army of A.I. robots
Comic Strips
Keywords: Action and adventure comics; Cartoons and comics; Funny animal comics